2009
DOI: 10.1093/jxb/erp073
|View full text |Cite
|
Sign up to set email alerts
|

Complete blockage of the mevalonate pathway results in male gametophyte lethality

Abstract: Plants have two isoprenoid biosynthetic pathways: the cytosolic mevalonate (MVA) pathway and the plastidic 2-C-methyl-D-erythritol 4-phosphate (MEP) pathway. Since the discovery of the MEP pathway, possible metabolic cross-talk between these pathways has prompted intense research. Although many studies have shown the existence of such cross-talk using feeding experiments, it remains to be determined if native cross-talk, rather than exogenously applied metabolites, can compensate for complete blockage of the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 46 publications
2
43
0
Order By: Relevance
“…It was previously reported that the MVA pathway plays a more important role than the MEP pathway during reproductive development in Arabidopsis [62,63]. Another interesting phenomenon from our study is that the heterozygous dxr mutant plants set normal homozygous seeds, suggesting that, without the MEP pathway, the gametophytes, embryo sac or later-developed homozygous embryo can develop normally, consistent with the previous reports.…”
Section: Discussionsupporting
confidence: 92%
“…It was previously reported that the MVA pathway plays a more important role than the MEP pathway during reproductive development in Arabidopsis [62,63]. Another interesting phenomenon from our study is that the heterozygous dxr mutant plants set normal homozygous seeds, suggesting that, without the MEP pathway, the gametophytes, embryo sac or later-developed homozygous embryo can develop normally, consistent with the previous reports.…”
Section: Discussionsupporting
confidence: 92%
“…Plant sterols play important roles in reproductive developmental processes such as embryogenesis and male fertility (Clouse, 2002;Schaller, 2003;Suzuki et al, 2004Suzuki et al, , 2009). However, it has not been shown that sterols are required for endosperm development.…”
Section: Smo2s Are Required For Endosperm Developmentmentioning
confidence: 99%
“…A study of the FKP 1 mutant revealed that the HMGCS enzyme is important in the mevalonate pathway for developing the tapetumspecific organelle and the fertility of pollen (Ishiguro et al, 2010). A null allele of FKP 1 produced male gametophytes that were lethal before the elongation of the pollen tube, and its absence caused sterile male gametophytes (Suzuki et al, 2009). …”
Section: Pollen-specific and Pollen-related Genesmentioning
confidence: 99%